2012
DOI: 10.1016/j.jad.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety symptoms and disorder predict activity limitations in the elderly

Abstract: Background: In the elderly, little attention has been paid to anxiety both on a symptom

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 32 publications
2
32
0
9
Order By: Relevance
“…Despite being a non-clinical sample recruited from community organisations, the majority of participants reported avoidance behaviours which could contribute to functional impairment and social isolation. This finding supported previous research that found older adults restrict their activity to familiar and non-demanding situations to avoid anxiety [25].…”
Section: Discussionsupporting
confidence: 91%
“…Despite being a non-clinical sample recruited from community organisations, the majority of participants reported avoidance behaviours which could contribute to functional impairment and social isolation. This finding supported previous research that found older adults restrict their activity to familiar and non-demanding situations to avoid anxiety [25].…”
Section: Discussionsupporting
confidence: 91%
“…As condições crônicas desempenham papel importante na explicação da associação entre incapacidade funcional, restrição social, limitação em atividades instrumentais da vida diária, depressão e ansiedade 37 . Um maior número de morbidades em idosos está associado à pior qualidade de vida no domínio psicológico e pode contribuir para o advento de sentimentos negativos 38 .…”
Section: Variáveis/categoriasunclassified
“…Até 39% dos idosos que apresentam o transtorno têm uma condição de comorbidade psiquiátrica, principalmente do tipo ansioso. Os sintomas de ansiedade são particularmente incapacitantes com relação às atividades da vida diária e estão associados com pior status social e econômico e com condições médicas crônicas 37 .…”
Section: Variáveis/categoriasunclassified
“…7 Esto puede acarrear dificultades para el diagnóstico, especialmente cuando se toma en consideración que, conforme al DSM-IV, el diagnóstico de TAG no se puede llevar a cabo en presencia de afecciones médicas. 2 Las alteraciones cognitivas primarias, asociadas a manifestaciones somáticas secundarias de la ansiedad, alteran la capacidad de trabajo, las relaciones interpersonales y las actividades placenteras. El TAG también aumenta el riesgo de padecer episodios depresivos, comorbilidades somáticas, uso de sustancias -como alcohol-y la automedicación.…”
Section: Introductionunclassified
“…2 Consulta Externa, Servicios Clínicos del INPRFM. 3 Servicio de Hospitalización y Atención Psiquiátrica Continua de la Subdirección de Servicios Clínicos del INPRFM.…”
unclassified